Studies on the Pectic Substances of Plant Cell Walls: III. DEGRADATION OF CARROT ROOT CELL WALLS BY ENDOPECTATE LYASE PURIFIED FROM ERWINIA AROIDEAE - Konno, Haruyoshi (1982)
Pectate lyase was isolated from the cell extract of Erwinia aroideae. The enzyme was further purified to a high degree by a procedure involving ammonium sulfate fractionation and chromatography on CM-Sephadex C-50 and on Sephadex G-200. The enzyme attacked its substrate in an endo fashion and was more active on the sodium salt of acid-insoluble polygalacturonate or pectic acid than it was on the methoxylated pectin. The enzyme had an optimum pH at 9.3, was stimulated by calcium ions, and was completely inhibited by ethylenediaminetetraacetic acid. In addition, the reaction products showed an absorption maximum between 230 and 235 nm and reacted with thiobarbituric acid. These results indicate that the purified enzyme is an endopectate lyase. The endopectate lyase also had the ability to solubilize effectively the pectic fraction from the cell walls of carrot (Daucus carota) root tissue. The enzyme released 30.5% of the wall as soluble products and also liberated all of the galacturonic acid present in the walls. The total neutral sugars released by the enzyme were 10.6% of the walls, which corresponded to 71.5% of noncellulosic neutral sugars. The soluble products were separated into five fractions by DEAE-Sephadex A-50 column chromatography. Based on the analysis of sugar composition of each fraction, the pectic fraction of carrot cell wall is presented.